Sequential Prefrontal and Temporoparietal Repetitive Transcranial Magnetic Stimulation (rTMS) for Treatment of Tinnitus With and Without Comorbid Depression: A Case Series and Systematic Review - Marder, Katharine G.; Cho, Janice; Chincanchan, Ruth; Wilson, Andrew C.; Corlier, Juliana; Krantz, David E.; Ginder, Nathaniel D.; Lee, Jonathan C.; Wilke, Scott A.; Tadayonnejad, Reza; Levitt, Jennifer; Ishiyama, Akira; et al. (Frontiers in Neurology, 2022)
Background: Tinnitus distress is related to both the loudness and intrusiveness of the tinnitus percept. Treatment approaches targeting both attentional/limbic and auditory systems may better alleviate tinnitus distress than approaches targeting the auditory system alone. Materials and Methods: Ten subjects with chronic tinnitus received sequential rTMS treatment involving: 1) excitatory stimulation administered to the left dorsolateral prefrontal cortex (DLPFC) or inhibitory stimulation administered to the right DLPFC, followed by 2) inhibitory stimulation administered to primary auditory cortex (Heschel’s gyrus or HG). A systematic literature review was performed to evaluate the existing literature on sequential repetitive Transcranial Magnetic Stimulation (rTMS) treatment approaches for tinnitus. Results of the case series are interpreted in the context of tinnitus neurobiology and the extant literature. Results: Subjects experienced a significant decrease (average 20%) in symptoms on the Tinnitus Functional Index (TFI). Those with tinnitus alone experienced a greater mean symptom reduction than those with comorbid MDD (25% vs. 17%, respectively). Adverse effects were transient and minor. Literature review confirmed that sequential approaches had some advantages compared to single site rTMS; in general, the addition of 1 Hz treatment at DLPFC was superior to single site rTMS in the short term (1-12 weeks), while the addition of 20 Hz treatment at DLPFC appeared superior in the long term (90-180 days). Conclusions: Sequential rTMS approaches for the treatment of tinnitus—particularly those administering low-frequency treatment at left DLPFC—merit further investigation.